2002
DOI: 10.1034/j.1600-0501.2002.130603.x
|View full text |Cite
|
Sign up to set email alerts
|

Histological assessment of augmented jaw bone utilizing a new collagen barrier membrane compared to a standard barrier membrane to protect a granular bone substitute material

Abstract: Successful bone augmentation requires predictable space maintenance and adequate exclusion of those cells that lack osteogenetic potential from the defect area. Natural bone mineral is considered to be osteoconductive and is used as space maker in combination with membrane barrier techniques. The aim of this study was to compare qualitative histological results achieved by using deproteinized bovine bone mineral (DBBM) as a space maintainer and a new collagen barrier (Ossix, test group) vs. the same bone subst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
131
0
5

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 135 publications
(141 citation statements)
references
References 24 publications
5
131
0
5
Order By: Relevance
“…No autogenous bone was used. For easier application, a coagulum was formed by the calcium phosphate grafting material with 1 to 2 ml of the patients' own blood collected in the wound area after the incisions were carried out Friedmann, et al, 2002);Friedman, et al, 2009). The composite grafting material was placed in the defect up to the level of the machined surface of the implant, in the vertical direction and up to the completion of the bony envelop in the lateral direction.…”
Section: Introductionmentioning
confidence: 99%
“…No autogenous bone was used. For easier application, a coagulum was formed by the calcium phosphate grafting material with 1 to 2 ml of the patients' own blood collected in the wound area after the incisions were carried out Friedmann, et al, 2002);Friedman, et al, 2009). The composite grafting material was placed in the defect up to the level of the machined surface of the implant, in the vertical direction and up to the completion of the bony envelop in the lateral direction.…”
Section: Introductionmentioning
confidence: 99%
“…18 El efecto barrera es más difícil de conseguir con las membranas reabsorbibles, por lo que al utilizar estas membranas se recomienda colocar material de injerto bajo ellas. 19 La literatura no muestra diferencias estadísticamente significativas entre el empleo de membranas reabsorbibles y no reabsorbibles en general, 20,21 aunque está publicado un mayor volumen de regeneración ósea con membranas no reabsorbibles alrededor de implantes colocados post-exodoncia. 22 En el trabajo publicado por Chia- pasco y cols.…”
Section: Guided Bone Regeneration (Gbr)unclassified
“…18 The barrier effect is more difficult to achieve with absorbable membranes so it is recommended that graft material be placed under these membranes. 19 The literature does not generally show statistically significant differences between the use of absorbable and nonabsorbable membranes, 20,21 but a larger volume of bone regeneration is reported with nonabsorbable membranes in implants placed after tooth extraction. 22 In the study reported by Chiapasco et is covered with a membrane.…”
Section: Injertos Particuladosmentioning
confidence: 99%
“…The best known groups of polymers used for medical purposes are aliphatic polyesters and collagen. Over the past decade membranes are made of polyglycolide, polylactide or copolymers thereof or of collagen (Hutmacher & Hürzeler 1995, Tal et al 1991Tal & Pitaru 1992;Moses et al 2005, , Friedmann et al 2002, von Arx et al 2001, Rothamel 2005. The qualities of a wide variety of bioresorbable membranes have been investigated experimentally and clinically (Lundgren et al 1994;Mayfield et al 1997;Simion et al 1997;Zitzmann et al 1997;Buser et al 1999, Tal et al 2008aTal et al 2008b).…”
Section: Bioresorbable Membranesmentioning
confidence: 99%
“…It is generally agreed that collagen membranes show a lower incidence of spontaneous exposure to the oral environment compared with non-resorbable membranes, and unlike non-resorable membranes, soft tissue healing following exposure of collagen membranes involves no infection (Friedmann et al 2002;Moses et al 2005). In a comparative study between prematurely exposed non-resorbable membranes (ePTFE), non-cross-linked collagen membranes (BioGide) and cross-linked collagen membranes (Ossix), the latter were claimed to be superior, and capable of supporting healing (Moses et al 2005).…”
Section: Collagen Barrier Membranes Exposed To the Oral Environment Bmentioning
confidence: 99%